El cartel europeo : 1888-1938 : 18 junio-16 septiembre 2012, Museo Picasso Málaga / [José Almada Negreiros ... et al. ; comisario, Carlos Pérez] - Negreiros, Almada (1893-1970) Pérez, Carlos (1947-2013)
Bibliografía: p. [98]-100